Teleduc - Workshop of Philosophy at Dom Jose Public School - Gonçales Filho, Gentil (Revista Brasileira de Aprendizagem Aberta e a Distância, 2018)
Experience report accomplished with some High School pupils of State School “Dom Jose de Camargo Barros” from Indaiatuba, SP, in the discipline of Philosophy, who have been using TelEduc learning virtual environment named “Workshop of Philosophy at Dom Jose Public School - both synchronous and asynchronous, since July 2005. The article presents the performance of the pupils in the main environment tools and the results of two surveys about the use and evaluation made by the pupils during the presencial teaching in the discipline and in the suggested proposals for research carried outside thef classroom.